2022
DOI: 10.1177/00812463221129362
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of the future time perspective in the relationship between global climate change awareness and hope for the prevention of climate change

Abstract: This study examined the mediating role of the future time perspective in the relationship between climate change awareness and the hope of preventing the climate emergency. The study group consisted of 398 adults. The data were collected using the awareness scale of university students about global climate change, climate change hope scale, and the Zimbardo time perspective inventory future time perspective subscale. The data were analyzed by SPSS 25.0, LISREL 8.70, and PROCESS v3.4 for SPSS. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Sangervo et al found climate anxiety and climate hope to be strongly related to each other [ 36 ]. Experts have recently begun exploring ways to transform the helplessness created by climate change into hope and to enhance individuals’ awareness of climate change in order to support environmentally friendly behaviors [ 37 ]. In a study conducted with young people in Australia, participants mentioned feeling hopeless and powerless because they believed they were not in a position to mitigate the effects of climate change [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sangervo et al found climate anxiety and climate hope to be strongly related to each other [ 36 ]. Experts have recently begun exploring ways to transform the helplessness created by climate change into hope and to enhance individuals’ awareness of climate change in order to support environmentally friendly behaviors [ 37 ]. In a study conducted with young people in Australia, participants mentioned feeling hopeless and powerless because they believed they were not in a position to mitigate the effects of climate change [ 38 ].…”
Section: Discussionmentioning
confidence: 99%